(NzEMNOE QDRO I WEKOWYE GEOMAGNITNYE WARIACII (B/s - (NkALININ(B, (N`RIJ dMITRIEWI^s; (NbENXKOWA(B, (Nn(B.(Np(B.s ((NkRASNOQRSK (B:s (Nif(B,s, 1987)
(NbIBLIOGR(B.: (NS(B. 97-113 (312 (NNAZW(B.)s
(Nan sssr(B, (NsIB(B. (NOTD(B-(NNIE(B, (NiN(B-(NT FIZIKI IM(B. (Nl(B.(Nw(B. (NkIRENSKOGOs
Keywords: (NzEMLQs; (NmAGNITNOE POLE zEMLIs